Pendidikan Baca Tulis Al-Quran (BTQ) di SMK Muhammadiyah Jawa Timur (Studi Kasus Pembelajaran BTQ di SMK Muhammadiyah 1 Taman Sidoarjo) - Rafi Andi Wibawa (Halaqa: Islamic Education Journal, 2018)
In this study formulated two problems, namely how the ability of students SMK Muhammadiyah 1 Taman in reading the Qur'an and how the factors that cause the inability of students SMK Muhammadiyah 1 Taman in reading the Qur'an. Objectives are achieved to determine the ability to read students SMK Muhammadiyah 1 Taman in reading the Qur'an and know the factors that cause students unable to read the Qur'an.The type of research used qualitative research. Qualitative research is intended to researchers do not treat so that data obtained in the form of data in accordance with events in the field. Data collection techniques use observation, interviews, and documentation. Data analysis technique is done by three stages, namely data reduction, data presentation, and conclusion drawing.The results of this study can be seen that the ability to read students SMK Muhammadiyah 1 Taman in reading the Qur'an can still be said in basic skills. The learning process of BTQ extracurricular activities conducted at SMK Muhammadiyah 1 Taman is in accordance with the guidance and guidance that exist but the implementation is different because of the lack of time that must collide with other extracurricular. Thus it can be concluded that the improvement of students' reading ability is still slow. This can be influenced by several factors such as the execution time of BTQ extracurricular activities, the supporting tools of BTQ activities which are still minimal and only using the Teachers book, as well as internal and external factors of the students themselves.